Effects of early-life stress on probabilistic reversal learning and response perseverance in young adults - Franco, Corinna Y.; Knowlton, Barbara J. (Neurobiology of learning and memory, 2023)
•Individuals who report experiencing early-life stress demonstrate greater perseveration after contingency reversal.•Sexual abuse and emotional neglect during childhood showed the most robust association with reduced cognitive flexibility.•Perseveration after reversal in the probabilistic classification task was associated with greater alcohol consumption. Early life stress (ELS), including experiences with abuse and neglect, are related to several negative health outcomes in adulthood. One area that has received attention is the increased rate of substance abuse disorder in individuals who had experienced ELS. Given the critical role habitual behavior in the development of substance abuse, ELS may affect the trajectory of neural development such that habitual responding is more dominant than in individuals who did not experience ELS. Here, we examine learning of a probabilistic classification task (the Weather Prediction Task) in healthy young adults who reported significant ELS and those that did not. This task can be learned in a declarative, model-based manner, or in a more habitual, stimulus-response manner. Participants learned to choose the outcome (sun or rain) that was probabilistically associated with each cue combination through reinforcement on each trial. After 100 trials, the probabilities were reversed, and we conceptualized habitual behavior as perseverating responses based on the old probabilities. We also collected information about subjective socio-economic status (sSES), anxiety, depression, and substance use from participants. Using multiple regression, we found that our measure of habitual responding was correlated with reported alcohol use, suggesting that our measure of habit has validity for health behaviors. Furthermore, we found that some forms of early life stress led to greater response perseverance after contingencies were reversed. Overall, the results suggest that childhood adversity may contribute to the development of habit.